MODERNIZATION OF EDUCATION FOR STUDENTS OF UKRAINIAN LANGUAGE AT MASARYK UNIVERSITY IN BRNO - MICHÁLIKOVÁ, Jitka (Comparative Legilinguistics, 2012)
This article is focused on the presentation of Ukrainian Studies – one of the specialized programs offered at the Department of Slavonic Studies at the Faculty of Arts, Masaryk University in Brno. Political, economic, and business relations between the Czech Republic and Ukraine deepened profoundly after 1991, as a consequence of Ukraine's independence. This resulted in an inclusion into the Ukrainian language program of a subject dealing with the issues of law terminology as well as translation of official, judicial and other juridical documents. This article shows not only the conception of the course “Ukrainian Language in the Domain of Law“ but also another activities of the department which are related to the language of law – for example organizing Ukrainian-Czech terminology seminaries in co-operation with the Chamber of Court Appointed Interpreters and Translators of the Czech Republic. The problems in translation of law terminology from and into Czech language are outlined as well. So far, these issues have not been thoroughly researched and that is why there is the need for specialists in philology, especially in Ukrainian philology.